2020
DOI: 10.1172/jci133934
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm influences induction of trained immunity by BCG vaccination

Abstract: BACKGROUND. The antituberculosis vaccine bacillus Calmette-Guérin (BCG) reduces overall infant mortality. Induction of innate immune memory, also termed trained immunity, contributes toward protection against heterologous infections. Since immune cells display oscillations in numbers and function throughout the day, we investigated the effect of BCG administration time on the induction of trained immunity. METHODS. Eighteen volunteers were vaccinated with BCG at 6 pm and compared with 36 age-and sex-matched vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 76 publications
2
88
1
Order By: Relevance
“…Previous studies have reported seasonal and circadian patterns in antibody titres in humans, 54 IgM 55 , often discovered serendipitously in the course of other investigations. 55 Leucocytes collected at different times of year showed decreased ex vivo response (thymidine incorporation, cytokine release) to activation in winter time in humans and rats [56][57][58]59 , and diurnal patterns in antibody titres 60 and in ex vivo response to stimulation of PBMCs 61,62 have been reported in humans. This study in UK Biobank is the first to investigate circadian and seasonal patterns in antibody titres to common infectious agents at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported seasonal and circadian patterns in antibody titres in humans, 54 IgM 55 , often discovered serendipitously in the course of other investigations. 55 Leucocytes collected at different times of year showed decreased ex vivo response (thymidine incorporation, cytokine release) to activation in winter time in humans and rats [56][57][58]59 , and diurnal patterns in antibody titres 60 and in ex vivo response to stimulation of PBMCs 61,62 have been reported in humans. This study in UK Biobank is the first to investigate circadian and seasonal patterns in antibody titres to common infectious agents at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…A number of COVID-19 vaccine candidates have shown extremely promising results [ 26 ], which is expected to be used in the near future. Current treatment strategies of COVID-19 include symptomatic treatment and supportive care (oxygen, mechanical and circulatory support).…”
Section: Overview Of Covid-19mentioning
confidence: 99%
“…BCG vaccination given in morning induces stronger trained immunity and adaptive immune phenotype after two weeks to three months compared to the evening vaccination in healthy adult volunteers [267]. Overall no trained immunity induces in people given evening vaccination.…”
Section: Targeting Immune Cell Metabolism During Severe Covid-19mentioning
confidence: 87%
“…The morning BCG vaccine receivers show an increase in circadian clock genes CLOCK and Aryl hydrocarbon receptor nuclear translocator-like protein 1 (ARNTL) or brain and muscle ARNT-like 1 (BMAL1) expression in their monocytes after one month along with an increase in histone 3 lysine 27 acetylation (H3K27ac, an epigenetic modification associated with gene activation) at the promoter of CLOCK and ARNTL genes [267]. The genes responsible for mTOR signaling (crucial for trained immunity induction) become more chromatin accessible in the morning vaccinated group, whereas evening vaccinated group show an increased chromatin accessibility to TNF and Nod-like receptor (NLR) signaling [267]. Morning receivers of BCG vaccine also show an increased transcription factor (TF) levels involved in mTOR signaling.…”
Section: Targeting Immune Cell Metabolism During Severe Covid-19mentioning
confidence: 99%